Analysis of Deformations of the Tunnel Excavation Face via Simplified Calculation Methods - Alireza Kalantar; Pierpaolo Oreste (Applied Sciences, 2023)
The stability of the excavation face during the excavation of a tunnel is necessary to safeguard the lives of workers and to guarantee regular and rapid progress of the works. In this paper, the stability conditions of the tunnelling face were analysed using simplified numerical calculation methods (one-step approach) and analytical methods, in order to evaluate the extrusion of the tunnelling face as a representative quantity of the mechanical behaviour of the rock ahead of it. A comparison between the numerical method and the hemispherical method was illustrated, which was able to demonstrate how the latter can be used with high reliability in this type of study. An extensive parametric analysis of the typical conditions encountered in the excavation of tunnels in weak rock made it possible to determine the extent of the face extrusion and the effect on it of the main considered geometric and geomechanical parameters. Thanks to the comparison of the extrusion values obtained from the calculation with the limit value indicated by the scientific literature, it is possible to arrive at a rapid assessment on the stability of the face. A specific study on the role of the pressure applied to the face on the extent of the extrusion then made it possible to understand how to proceed to define the intensity of the main stabilisation systems (TBM thrust and longitudinal fiberglass bolts) to avoid the risk of collapse of the excavation face.